Factors Impacting the Success of Malaysian Internet Entrepreneurs - Seri Anis Binti Sofian (Human Sustainability Procedia, 2018)
The purpose of this study is to identify the factors impacting the success of Internet entrepreneurs in Malaysia. Literatures pointed out the potential factors that may affect the success of Internet entrepreneurs are, Managerial factor, Market factor, Financial factor and Customer Satisfaction. The development of questionnaires is based on this factors and adaptation from previous studies. Data have been collected through online survey method by distributing the questionnaires to identified Internet entrepreneurs by e-mail. The email consists of link to the online survey at Google Docs.com. (Link: http://goo.gl/forms/YGBggNgQ8x). Additionally, data were also been manually distributed to fashion vendor which integrating Internet facilities in their business operations. Out of 200 questionnaires distributed only 150 were returned. The data analysis carried out using Statistical Package for Social Sciences (SPSS) software version 21.0. Multiple regressions were used to analyse the data and testing the hypothesis. The result suggests Managerial factor have significant and positive relationship in predicting the success of Malaysian e-business and Internet entrepreneur. Managerial factor Beta coefficient value is the highest among all. Whereas, the other three factors; Market, Financial and Customer Satisfaction does not have a strong relationship towards the determination of success Malaysian Internet entrepreneurs. Although Marketing factor shows a significant relationship, however it is in negative direction. Therefore, the proposed hypothesis on the Market factor relationship towards the success Malaysian e-business and Internet entrepreneur does not supported. The study on the success factors that impact the success of an Internet entrepreneur suggests there are implications theoretically where it has supported some of the earlier research. At same time, this research also identified the success factors that have impact on the successful of Internet entrepreneur particularly in Malaysia. In addition, the identified relationship of the success factors can become as an additional knowledge to the new start-up and existing Internet entrepreneur in Malaysia to gain wealth by exploiting the opportunities of Internet in their Internet-based firm.